Exploring traditional madrasahs and islamic integrated schools in Zanzibar - Malengo, Ali Faki
This case study research sought to investigate the realities of Traditional Madrasahs and Islamic Integrated Schools in order to reveal their strengths and weaknesses, and subsequently to make recommendations for a reformation of religious education in Zanzibar. In this study, a total of 138 respondents from six schools were involved. For qualitative part, six headmasters and 12 teaching staff were purposively selected based on the length of their teaching experiences, while for quantitative side, 120 students were selected based on some criteria as stipulated in this work. Both qualitative and quantitative research instruments namely in-depth interview and questionnaire respectively were used to collect data on the investigated aspects. The interview data were transcribed, coded, classified, and analysed using thematic content analysisprocedures or steps. The data collected via questionnaires were analysed using SPSS software Version 23 and the results are reported mainly as descriptive statistics. Observation was adopted only to gain additional insights to complement the findings obtained through the use of the above two instruments. The main findings of this study include: 1) Madrasahs in Zanzibar provide religious knowledge that mainly focuses on preparing the students for the life success in the Hereafter, while Islamic Integrated Schools provide conventional knowledge that centres on the worldly success; 2) although the teaching methods used in the schools are to a large extent bringing about positive effect in teaching and learning, there are other factors that have interfered the effective use of those methods; 3) the murabbi concept is theoretically well understood and practically demonstrated by the teachers, and the students to a large extent do appreciate their teachers and the learning process; 4) the human, material, and financial resources in madrasahs are more inferior compared to that of Islamic Integrated Schools; 5) the schools' extra-curricular activities are mostly reflective of the realisation of the schools' philosophy; and 6) the cooperation among the schools' management, the teaching staffs, and the students is good, although the parents' and other stakeholders' cooperation in the community is very minimal. On the basis of these findings, the study has proposed some recommendations, including the improvement of the educational philosophy and the broader concept of integrated knowledge and subsequently the course contents used in both types of schools. These recommendations are necessary, if the reformation of religious education in Zanzibar is to be realised. Additionally, there is a need for other investigators to attempt other studies which can cover a larger scope involving bigger numbers of respondents, especially through the use of quantitative research strategies.